Human in the socio-economic determinants of environmental protection - Trzewik, Jacek (Studia Ecologiae et Bioethicae, 2017)
In recent years, the issue of the position of human beings within their relationship with the environment takes on particular importance. Expression of this trend is for instance the gradual extension of the acquis that provides for certain symptoms of rights of individuals, the implementation of which is essential for achieving the objectives of environmental protection. It is, therefore, reasonable to attempt to consider the economic and axiological determinants of actions known as environmental protection. Hence the identification of anthropocentric basis and axiological sources of undertaken of the human environmental protection, are the subject of this study.